The relationship between the wheat plants at different tap organozenesis and phytophagous, their harmfulness - Strygun, O.O.; Trybel, S.O.; Goncharenko, O.M.; SuddenkoY.М. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The basic types of herbivores wheat groups on their affinity to damage of the plants and their impact on the formative processes. It is shown that the constant pressure on the formative processes, inhibition of plant growth and development adversely affects the productivity and quality of grain. Calculated in terms of population of crops of pests, taking into account existing EPSH potential losses from individual groups of herbivores that exceed 5%. Showing actual average loss grain cereals from pests, which is 12.7%, which is evidence of the need to strengthen protective measures and reduce the actual loss to the level of <5%.